Study of concentric, eccentric and split type magnetic membrane micro-mixers - Shao Qiang Tang; King Ho Holden Li; Ze Ting Yeo; Wei Xuan Chan; Say Hwa Tan; Yong-Jin Yoon; Sum Huan Ng (Sensing and Bio-Sensing Research, 2018)
Electromagnetically driven elastic magnetic microfluidic mixers were investigated for their performance in air, water and glycerol filled chambers. They were fabricated by embedding flexible magnets in polydimethylsiloxane (PDMS) membrane. At a driving frequency of 100 Hz, oscillating fluid flow was induced and mixing was achieved. Three designs were fabricated and studied: a) concentric type with the magnetic material in the center of the membrane, b) eccentric type with the magnetic material offset from the center of the membrane and c) split type with two regions of magnetic materials with opposing polarities. The split configuration provides additional fluid folding, facilitating mixing of the 20 μL fluorescent dye in 60 μL of solvent. Simulation and experimental results show that the eccentric and split designs were able to achieve a 20–30% reduction in mixing time compared to the concentric design. At the same magnetic flux density, the eccentric type design exhibited the greatest deflection, explaining the better mixing achieved over the concentric type design. The split type design, having the lowest deflection, was able to perform better and more consistently than the eccentric type design by creating a “micro rocker mixer” effect. We postulated that the shapes of the deflection profiles in the eccentric and split designs contributed to the mixing efficiency by promoting better chaotic advection than the concentric design.